From violence to more violence in Central America - Medina, I (Refugee Studies Centre, University of Oxford, 2014)
Many Central American migrants flee their home country as a result of violence and threats from the criminal gangs. A large number of them also encounter the same type of violence that they are fleeing when on the migratory routes through Mexico